Literacy Learning Model Based on Surabaya’s Local Identities in Community-Based Libraries of Surabaya - Nur Wulan; Kukuh Yudha Karnanta; Ni Luh Ayu Sukmawati; Puji Karyanto (MOZAIK HUMANIORA, 2022)
This study investigates the ways bottom-up learning, specifically discovery and project-based learning, in strengthening local wisdom and identities among the youths in Surabaya. The local identities of Surabaya are generally associated with being egalitarian, urban, and multicultural. Despite the strong association of Surabaya with the bravery of Surabaya youths in the 1945 war against the Allied troops (semangat arek Suroboyo), young people of Surabaya nowadays do not internalize the spirit strongly. Our preliminary observation suggests the fact, and this can be seen from their writings before joining the writing class that we conducted. In coordination with the Public Library of Surabaya (Municipal Library and Archive of Surabaya) and community-based libraries in Surabaya, this experimental research was conducted to gain insights on the extent to which discovery and project-based learning can stimulate junior high school students to be more aware of their locally rooted identities. The study shows that the application of the student-centered learning methods can contribute significantly to the internalization and representation of Surabaya identities reflected in the students’ writings.